Adipose-Derived Mesenchymal Stem Cell-Derived Extracellular Vesicles Rescue Tendon Injury in Rat via the miR-19 a/IGFBP3 Axis - Haibo Zhao; Hongyuan Jiang; Haoyun Zhang; Zewen Sun; Qian Lin; Tianrui Wang; Tengbo Yu; Yingze Zhang (Stem Cells International, 2022)
Purpose. Adipose-derived mesenchymal stem cells (ADSCs) are increasingly applied in tendon repair. However, the underlying mechanisms of ADSC-derived extracellular vesicles (EVs) in tendon healing are largely unknown. In this study, we investigated the effect of the EVs secreted by ADSCs on the recovery of tendon injuries and its potential mechanism. Materials and Methods. We injected ADSCs into the injured tendon, followed by the evaluation of the tissue morphology, tenocyte proliferation, and oxidative stress. Then, the injured tenocytes were treated with EVs secreted by ADSCs, and oxidative stress and proliferation of tenocytes in vitro were detected. After the overexpression and knockdown of miR-19a and its target protein IGFBP3, the oxidative stress and proliferation of tenocytes in vitro were assessed. Finally, the injured tendon was treated with EVs, and the tissue morphology and proliferation of the injured tendon in vivo were examined. Results. ADSC-derived EVs were found to inhibit oxidative stress and promote proliferation of tenocytes isolated from an injury model of rats. EVs were shown to carry miR-19a which regulated the expression of IGFBP3 through binding to 3′UTR of IGFBP3 mRNA. In addition, IGFBP3 promotes oxidative stress and inhibits proliferation of tenocytes. Finally, we found that ADSC-derived EVs promoted tendon wound healing in vivo. Conclusions. Our data suggest that treatment with ADSC-derived EVs ameliorates tendon injury by inhibiting oxidative stress and promoting proliferation in tenocytes. miR-19a carried by ADSC-derived EVs regulates IGFBP3 expression through binding to its 3′UTR.